Geochemistry of hematitite and itabirite, Quadrilátero Ferrífero, Brazil - Selmi,Moustafa (2009)
Twenty-one samples of hematitite and twelve samples of itabirite were collected from different deposits of the Quadrilátero Ferrífero (QF) area and were analyzed for trace and rare earth elements. The purpose of the study is to understand the element distribution in the QF in comparison with other iron formations (IF) around the world. Trace element contents are relatively low with considerable variability, being lower than the contents in the Algoma IF, Anamikie IF, Maru IF in Nigeria and Orissa IF in India. REE's abundance is relatively low, but higher than REE's of Hamersley IF of Western Australia, Surgur belt in India and lower than Kuruman IF in South Africa. Chondrite normalized patterns show slight degrees of fractionation for LREE to HREE and slightly positive Eu anomalies coupled with positive values of (La/Yb)CN and (La/Sm)CN ratios.